ANALISIS SISTEM DRAINASE PADA DAERAH ALIRAN SUNGAI TUKAD MATI, KABUPATEN BADUNG – BALI - AAA Made Cahaya Wardani; Cokorda Putra; Luh Azhanova (UNHI PRESS, 2026)
The Tukad Mati River Basin (DAS) is a crucial hydrological system in urban Bali, particularly in the Kuta area and its surroundings. This river serves as the main urban drainage channel and controls rainwater runoff. However, in recent years, this area has frequently experienced inundation and flooding due to various factors such as sedimentation, land use changes, and limited drainage system capacity. This research examines the characteristics of the Tukad Mati watershed, drainage system issues, and alternative solutions based on civil engineering and hydrological approaches.